Аналітичне дослідження перспективи процесів автоматизації прийому, оцінки якості та закладання зерна на зернопереробних підприємствах - Чурсінов, Ю. О.; Tchoursinov, Yu.O.; Ковальова, О. С.; Kovaliova, O.S.; Калина, В. С.; Kalyna, V. S.; Пилипенко, Г. О.; Pylypenko, G.; Хомик, Н. І.; Khomyk, N.; Lehmann, Ch. (Таврійський державний агротехнологічний університет, 2020)
Розглянуто питання обґрунтування використання сучасних логістичних схем прийому, перерозподілу, вивантаження, оперативного визначення якості та направлення потоків зернових мас по призначенню на елеваторах, зернопереробних підприємствах, які переробляють насіння злакових і олійних культур. В нашому конкретному випадку досліджено цілеспрямованість виконання комплексного процесу логістики – прийому, відбору проб, якісного та швидкого автоматизованого аналізу зернових продуктів, рішенням щодо усунення вузьких місць загальної зернопереробної системи. Запропоновано проект концепції INOGET, що передбачає вимоги програмно-логістичного комплексу, який складається з реєстрації водія, автоматизованого відбору проб та аналізу, контролю справжності та контролю процесу прийому, враховуючи обмін контактами з існуючою системою управління процесом. Необхідною умовою для цього є автоматизація всіх відповідних етапів процесу – це єдиний спосіб оптимізувати логістичний процес у значній мірі. У рамках встановлення об’єктів спрощено потік транспортних засобів на території підприємства. Для уникнення існуючого протилежного руху, вихід рекомендовано перенести на інший бік підприємства. The questions of the rationale for the use of modern logistic schemes for receiving, redistributing, unloading, operational determination of the quality and direction of the flows of grain masses for their intended purpose at elevators, grain processing enterprises that process seeds of cereal and oilseeds are considered. In our particular case, the purposefulness of the implementation of the integrated logistics process was studied – receiving, sampling, high-quality and fast automated analysis of grain products, the decision to eliminate bottlenecks in the overall grain processing system. The project of the INOGET concept has been republished, transferring the vimogs to the program-logic complex, storing it from the registration water, automated sample collection and analysis, reference monitoring and monitoring the process of reception, and the possibility of exchanging the contacts with the necessary information. A neces – sary mind for the whole є automation of all of these processes is the process of optimizing the logistic process of a significant world. Components such as upgrading existing freight duplex grain scales are recommended; mandatory is the presence of a longitudinally automatic sampler that provides sampling according to the scheme of the full length of the vehicle; automatic pneumatic transportation of samples and sample preparation to the laboratory; program Bitzer, taking into account special programming; driver self-service on the territory of the enterprise. Acceptance process is accelerated due to the fact that all separate processes from vehicle registration, sampling, weighing and grain analysis processes to preparation of invoices for various vehicles can work in parallel through sequential automation.
Perspective analytical study reception automation processes, quality assessment and grain laying at grain processing production
Keywords: технологічний комплекс; technological complex; автоматизація; automation; логістика; logistics; оцінка якості; quality estimation; система; system; процеси; processes; зернові потоки; grain flows; зважування; weighing; транспортні засоби; transport vehicles